(6x-22)-(x+31)=Y

Simple and best practice solution for (6x-22)-(x+31)=Y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x-22)-(x+31)=Y equation:


Simplifying
(6x + -22) + -1(x + 31) = Y

Reorder the terms:
(-22 + 6x) + -1(x + 31) = Y

Remove parenthesis around (-22 + 6x)
-22 + 6x + -1(x + 31) = Y

Reorder the terms:
-22 + 6x + -1(31 + x) = Y
-22 + 6x + (31 * -1 + x * -1) = Y
-22 + 6x + (-31 + -1x) = Y

Reorder the terms:
-22 + -31 + 6x + -1x = Y

Combine like terms: -22 + -31 = -53
-53 + 6x + -1x = Y

Combine like terms: 6x + -1x = 5x
-53 + 5x = Y

Solving
-53 + 5x = Y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '53' to each side of the equation.
-53 + 53 + 5x = 53 + Y

Combine like terms: -53 + 53 = 0
0 + 5x = 53 + Y
5x = 53 + Y

Divide each side by '5'.
x = 10.6 + 0.2Y

Simplifying
x = 10.6 + 0.2Y

See similar equations:

| 12d-2d(8+6e)+11de=0 | | 8c=48 | | -4x-14=2 | | 51+2x+x=180 | | -13(z-3)= | | sp-11=p+5 | | 1.4w+5.2=1.2w+4.3 | | 4j+5=-91 | | 198=-11r | | 1.4w+5.2=1.2+4.3 | | (61+64-124)= | | 3(x-4)-4=-16 | | 4-2x=10-x | | 85+63+x=180 | | 26=(-2)(3)+x | | 28=m+3m | | 48=n+7 | | (-3)2+(-4)(-9)= | | 85+95+x=180 | | 4x+8=-x+-7 | | 28=9a-15-39 | | 6(2x-1)=11x | | 9x+3=9(x-3) | | .25x=4.9 | | 1+-2x=0 | | (X+2)(x+0.5)(x-4)=0 | | -1+-1x=0 | | -11+6x=-23 | | x+x+1+65=180 | | 7(x+2)+4(2x-3)=46 | | (6x+13)+(14x-33)=90 | | -1.3y=3-x |

Equations solver categories